2021
DOI: 10.1007/s11325-020-02276-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the sleep variables contributing to excessive daytime sleepiness among patients with obstructive sleep apnea

Abstract: Purpose Excessive daytime sleepiness (EDS) is a main symptom in patients with obstructive sleep apnea (OSA); however, patients with OSA have significant variability in their reported EDS which cannot be fully explained by the apnea-hypopnea index (AHI). The purpose of this study was to investigate gender differences regarding the sleep test variables contributing to excessive daytime sleepiness. Methods Retrospective study of 578 men and 270 women with sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It has been reported in the literature that for the elderly, weight loss usually leads to a decrease in fat and muscle mass, which may further impair the strength and effectiveness of the pharyngeal muscles, and lead to a more easily folded upper airway (Liu et al, 2021). It was previously found that BMI is associated with sleepiness in men, while ESS is not associated with BMI in women with OSA (Honig, Green, & Daga, 2021). Therefore, the predictors of gender, age, DBP, BMI, NC and ESS are all related to OSA, and they were deemed reasonable for the construction of the model.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported in the literature that for the elderly, weight loss usually leads to a decrease in fat and muscle mass, which may further impair the strength and effectiveness of the pharyngeal muscles, and lead to a more easily folded upper airway (Liu et al, 2021). It was previously found that BMI is associated with sleepiness in men, while ESS is not associated with BMI in women with OSA (Honig, Green, & Daga, 2021). Therefore, the predictors of gender, age, DBP, BMI, NC and ESS are all related to OSA, and they were deemed reasonable for the construction of the model.…”
Section: Discussionmentioning
confidence: 94%
“…Oliveira et al (24) concluded that insomnia symptoms are more common in elderly females, while another study reported that female gender was not an independent risk factor for sleep disorders (25). These differences may result from the methodological discrepancies of the studies as well as the fact that some hormonal and biological ones in both genders may affect sleep disorders (26).…”
Section: Discussionmentioning
confidence: 99%